The Cognitive–Affective Asymmetry of Animated Video in Elementary Character Education - Dody Filado; Haryanto; Troy (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
Indonesian development research on animated video for character education routinely reports effectiveness for both cognitive and affective outcomes. Most such conclusions, however, rest on one-group pretest-posttest designs and self-report instruments vulnerable to testing, ceiling, and social desirability effects. The present study used the prevailing template deliberately, to examine the gap between what it can detect and what it claims. An animated video on rights, obligations, and responsibility, built with the Alessi and Trollip model, was tested with seventeen fifth-grade students at a public elementary school in Kepanjen, Malang. The cognitive test produced a normalised gain of 0.37, classified as medium but constrained by an already high pretest baseline. The responsibility self-report shifted by only two percentage points, well within measurement noise, with both measurements compressed against the very high category. This asymmetry between a moderate cognitive gain and a negligible affective shift is not idiosyncratic; it is what short multimedia interventions tend to produce when affective outcomes are read as dispositional traits rather than process variables. Animated video supported knowing but, within this study, produced no comparable movement in becoming. The product itself passed expert validation in the feasible to very feasible range. The asymmetry is better read as a property of the prevailing evaluation template than of the product alone, and concerns what a one-group, self-report design can detect, independent of sample size. For researchers and curriculum developers, affective effectiveness should not be inferred from short single-session designs; designs, instruments, and durations must match the dispositional nature of character.